Cardiovascular Effects of Epinephrine During Experimental Hypothermia (32°C) With Spontaneous Circulation in an Intact Porcine Model - Mohyuddin, Rizwan; Dietrichs, Erik Sveberg; Sundaram, Predip; Kondratiev, Timofey; Figenschou, Marie Fjellanger; Sieck, Gary C.; Tveita, Torkjel (Frontiers in Physiology, 2021)
Aims: Rewarming from accidental hypothermia and therapeutic temperature management could be complicated by cardiac dysfunction. Although pharmacologic support is often applied when rewarming these patients, updated treatment recommendations are lacking. There is an underlying deficiency of clinical and experimental data to support such interventions and this prevents the development of clinical guidelines. Accordingly, we explored the clinical effects of epinephrine during hypothermic conditions. Materials and methods: Anesthetized pigs were immersion cooled to 32°C. Predetermined variables were compared at temperature/time-point baseline, after receiving 30 ng/kg/min and 90 ng/kg/min epinephrine infusions: (1) before and during hypothermia at 32°C, and after rewarming to 38°C (n = 7), and (2) a time-matched (5h) normothermic control group (n = 5). Results: At 32°C, both stroke volume and cardiac output were elevated after 30 ng/kg/min administration, while systemic vascular resistance was reduced after 90 ng/kg/min. Epinephrine infusion did not alter blood flow in observed organs, except small intestine-flow, and global O2 extraction rate was significantly reduced in response to 90 ng/kg/min infusion. Electrocardiographic measurements were unaffected by epinephrine-infusion. Conclusion: Administration of both 30 ng/kg/min and 90 ng/kg/min at 32°C had a positive inotropic effect and reduced afterload. We found no evidence of increased pro-arrhythmic activity after epinephrine infusion in hypothermic pigs. Our experiment therefore suggests that β₁-receptor stimulation with epinephrine could be a favorable strategy for providing cardiovascular support in hypothermic patients, at core temperatures > 32°C.